Interest rate derivative markets in Hungary between 2009 and 2012 in light of the K14 dataset - Zalán Kocsis; Csaba Csávás; István Mák; György Pulai (Magyar Nemzeti Bank, 2013)
MNB has received daily, transaction-level data on key Hungarian interest rate derivatives markets since the beginning of 2009 with the launching of the K14 report. The dataset that has accumulated since early 2009 provides an opportunity to better comprehend the structure and functioning of these markets. The goal of the current paper is two-fold: to study the data from a monetary policy perspective and to present a descriptive type of analysis of these markets for those interested; from active market participants to analysts, researchers. An important finding from a central banking viewpoint is that interest rate expectations are the main motives for trading in the FRA market, hence price quotes are not biased by structural, risk management factors. However, the speculative and hedging motives are both present in the IRS market; the latter may alter pricing relative to expectations. The 3x6s in the FRA and the 2-year rates in the IRS market are respectively the most liquid and, hence, informationally the most reliable products. In the past years domestic banks positioned toward lower interest rates relative to foreign counterparties, though the extent of such open positions has changed over time. The empirical relationship between bank analyst rate expectations and FRA-positioning has been weak. However, in times of greater variation in analyst forecasts FRA-positions have varied more as well. In the CIRS market domestic banks' activities of hedging the balance sheet currency mismatch and of foreign exchange liquidity management have led to a structural extra demand of foreign currency receiving swaps, which also resulted in large (negative) CIRS spreads. The commonly used CIRS transactions in the Hungarian market are floating-floating type basis swaps, and thus they are basically not used for interest rate risk management.
Keywords: E 44; F31; F32; G01; 330; interest rate derivative; currency swap; forward rate agreement; financial crisis; counterparty limit; foreign exchange liquidity